Mapping a nosocomial outbreak of measles, coinciding with a period of sustained transmission in South London in 2018. Issue 4 (August 2020) - Vink, J.P.; Snell, L.B.; Bernard, K.; Mitchell, H.; Heathcock, R.T.; Cordery, R.; Newsholme, W.
Summary: A measles outbreak in London is described, involving 34 cases across two hospitals and a local community across two countries. After a single introduction to hospital, spread propagated via unvaccinated retail shop workers to healthcare staff, highlighting the importance of expanding occupational health policies to non-clinical hospital staff. Further spread into an under-vaccinated Traveller community is a reminder that measles can spread in the absence of herd immunity. Subsequently endemic measles transmission has been re-established in the UK.